CHARACTERISTICS OF BODY FAT PERCENTAGE AND IT’S DISTRIBUTION IN UDAYANA UNIVERSITY MEDICAL STUDENTS IN 2023 - Prameswari, Ni Nyoman Wulan Trisna; Primayanti, I Dewa Ayu Inten Dwi; Sundari, Luh Putu Ratna; Griadhi, I Putu Adiartha (E-Jurnal Medika Udayana; Vol 13 No 11 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i11.P14, 2024)
The composition of fat in the body can show the balance between intake and use of nutrients in the body. If the body has more nutritional intake than it uses, then the excess nutrients (carbohydrates and protein) will be stored in the form of reserve fat in the body. Continuous accumulation of reserve fat without sufficient physical activity can cause weight gain and obesity. Obesity can trigger cardiovascular disease, metabolic syndrome, diabetes, dyslipidemia, and others. This research was conducted to determine the characteristics of body fat percentage and its distribution in Udayana University medical students in 2023. This research used a cross-sectional observational design. The respondents of this research were medical students in the class of 2020–2022 at Udayana University who met the inclusion and exclusion criteria. The sampling technique uses proportional random sampling with a minimum sample size calculated using the Slovin formula. From 105 research respondents, it was found that 49.5% of them had normal body fat percentage. In male respondents, the proportion of body fat percentage was almost the same in the normal (42.9%) and high (40.5%) groups. In female respondents, the proportion of body fat percentage was quite large in the normal (55.6%) and low (22.2%) groups. Most of the respondents had normal waist circumference (74.3%) and normal waist-to-hip ratio (68.6%). Keywords: Body Fat Percentage, Body Fat Distribution, Waist Circumference, Waist-To-Hip Ratio, Medical Students.